Overview of dendritic cell-based vaccine development for leishmaniasis - Bagirova, M.; Allahverdiyev, A. M.; Abamor, E. S.; Ullah, I.; Cosar, G.; Aydogdu, M.; Senturk, H.; Ergenoglu, B. (WILEY, 2016)
Leishmaniasis is one of the most serious vector-borne diseases in the world and is distributed over 98 countries. It is estimated that 350 million people are at risk for leishmaniasis. There are three different generation of vaccines that have been developed to provide immunity and protection against leishmaniasis. However, their use has been limited due to undesired side effects. These vaccines have also failed to provide effective and reliable protection and, as such, currently, there is no safe and effective vaccine for leishmaniasis. Dendritic cells (DCs) are a unique population of cells that come from bone marrow and become specialized to take up, process and present antigens to helper T cells in a mechanism similar to macrophages. By considering these significant features, DCs stimulated with different kinds of Leishmania antigens have been used in recent vaccine studies for leishmaniasis with promising results so far. In this review, we aim to review and combine the latest studies about this issue after defining potential problems in vaccine development for leishmaniasis and considering the importance of DCs in the immunopathogenesis of the disease.
Keywords: dendritic cell; tropical disease; leishmaniasis; vaccination; CYTOTOXIC T-LYMPHOCYTES; MYELOID DC SUBSET; VISCERAL LEISHMANIASIS; CUTANEOUS LEISHMANIASIS; CLINICAL-TRIAL; LEISH-F1+MPL-SE VACCINE; IMMUNE-RESPONSES; MURINE MODEL; IN-VIVO; NUCLEOSOMAL HISTONES; Immunology; Parasitology